A determination criterion for predicting the outcome of oblique collision between an oil droplet and solid surface. (June 2017) - Fang, Long; Chen, Guoding; Liu, Deng
In a bearing chamber, oil droplets shed from the bearing impinge on the outer chamber housing with different angles. The outcome of oblique collision between an oil droplet and the outer chamber housing determines the flow characteristic of wall oil film which has an important meaning to realize the rigorous lubrication design in the bearing chamber. However, the study of predicting the outcome of oblique collision between an oil droplet and solid surface is relatively rare. In this paper, an experimental setup about oil droplet–solid surface oblique collision and a numeric calculation model using Volume of Fluid (VOF) method have been built. And a lot of experimental work and numerical calculations have been done in a wide range of conditions. Based on that, a determination criterion is ultimately established for predicting the outcome of oblique collision between an oil droplet and solid surface. With the experimental data from literatures and this paper, the determination criterion is verified. The research work in this paper is not only a foundation work for better understanding the conditions of lubrication in bearing chamber but also an important reference for the study of droplet–solid surface collision.